Pengaruh Polusi Udara terhadap Angka Kematian Dini Provinsi Banten di Daerah Cilegon - Leli Maliha Fadilah; Rizal Aditya Pratama; Akrom (Ar-Rasyid: Jurnal Publikasi Penelitian Ilmiah, 2026)
This study aims to analyze the effect of air pollution on premature mortality rates in Banten Province with a specific focus on Cilegon City as the most densely industrialized area at the western tip of Java Island. The main objectives of this research are to identify the dominant sources of air pollution, estimate the number of premature deaths caused by exposure to pollutants from industrial activities and coal-fired power plants, and formulate effective prevention strategies and environmental law enforcement. This study also seeks to measure the economic impact of premature mortality and healthcare costs borne by the community and government. Furthermore, the research aims to explore the social, educational, and ecological aspects affected by chronic air pollution in the region. By employing secondary data analysis from various environmental research institutions and case studies of law enforcement actions that have occurred, this research is expected to provide evidence-based policy recommendations for central and local governments in protecting the public's right to clean air and preventing thousands of avoidable deaths.